2019
DOI: 10.1016/j.cjtee.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms and treatments of muscular pathological changes in immobilization-induced joint contracture: A literature review

Abstract: The clinical treatment of joint contracture due to immobilization remains difficult. The pathological changes of muscle tissue caused by immobilization-induced joint contracture include disuse skeletal muscle atrophy and skeletal muscle tissue fibrosis. The proteolytic pathways involved in disuse muscle atrophy include the ubiquitin-proteasome-dependent pathway, caspase system pathway, matrix metalloproteinase pathway, Ca 2+ -dependent pathway and autophagy-lysosomal pathway. The importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Muscle protein degradation is notably elevated in disused muscle and thought to involve the ubiquitin-proteasome-dependent pathway, caspase system pathway, and autophagy pathway (Wang et al, 2019). Of these, the ubiquitin-proteasome system (UPS) mediates the degradation of short-lived proteins and has been indicated as an important mechanism in disuse atrophy (Malavaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle protein degradation is notably elevated in disused muscle and thought to involve the ubiquitin-proteasome-dependent pathway, caspase system pathway, and autophagy pathway (Wang et al, 2019). Of these, the ubiquitin-proteasome system (UPS) mediates the degradation of short-lived proteins and has been indicated as an important mechanism in disuse atrophy (Malavaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hindlimb immobilization is another method to induce muscle atrophy. Immobilization refers to holding a joint or bone in place with a cast to prevent its movement, thus inducing muscle contracture and atrophy (35,36). In contrast, the rodents are in a head-down position to simulate weightlessness for hindlimb unloading (37).…”
Section: Effects Of Astaxanthin On Skeletal Muscle: Evidence From In mentioning
confidence: 99%
“…1 The normal ROM is difficult to restore once lost even through surgical treatment, and immobilization is a major cause of knee joint contracture. 2 Two different structural components which contained myogenic contracture and arthrogenic contracture make contribution to joint contracture formation. 3 Studies on animal muscles have shown that passive extensibility depends on the size and length of the muscle fibers and the amount and arrangement of connective tissue in the muscle belly.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle atrophy is an important part of myogenic contracture. 2 Sustained muscle atrophy which caused by loss of tissue protein because of decreased synthesis and increased degradation, an increase in the amount of intramuscular connective tissue, and the arrangement of collagen fibrils in the endomysium severely affects the function of knee joint. 5 During the process of muscle atrophy from immobilization in shortened position, the mass of muscle was reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation